Immune Thrombocytopenia as the Initial Manifestation of Pediatric Systemic Lupus Erythematosus: Case Reports - Ringoringo, Harapan Parlindungan (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Immune thrombocytopenia (ITP) can precede the onset of systemic lupus erythematosus (SLE) by months to years. CASE PRESENTATION: A 12-year-old girl weighing 46 kg came to the hospital with the complaint of 12 days-menstrual bleeding. The patient is weak, pale. Eyes, ENT, heart, lungs, abdomen: within normal limits, no petechiae. Laboratorium: Hemoglobin (Hb) 4.6 g/dL, leukocytes 12,930/uL, platelets 11,000/uL, hematocrit 15%, Diff Count: normal. Red blood cell (RBC) 1.59 million/uL, mean corpuscular volume (MCV) 94.3fL, mean corpuscular hemoglobin (MCH) 28.9pg, MCH concentration 30.7%, RDW-CV 14.6%. Corrected-reticulocytes 5.16%, Ret-He 22.6, IPF 54.17%. Peripheral blood smears normochromic, normocytic, blast not found, platelets are rare. The diagnosis is menometrorrhagia with anemia due to bleeding caused by ITP. The patient was given PRC and platelet transfusion, methylprednisolone. Three months later, the patient had another prolonged menstruation, hair loss, no petechiae, or purpura. Laboratorium: Hb 8.2 g/dL, leukocytes 7800/uL, platelets 6000/uL, RBC 1.59 million/uL, MCV 94.3fL, MCH 28.9pg, corrected reticulocytes 5.08%, Ret-He 24.6, IPF 54.5%. ANA test positive, Anti dsDNA-NcX 190.2 IU/ml. The diagnosis is SLE. During the last 16 months, the patient took 10 mg prednisone with a platelet count >150,000/uL. CONCLUSION: In every case of ITP in a child, consider the possibility of SLE.